The Effect of Health Education through HIV/AIDS Booklet Media on Adolescent Behavior for HIV/AIDS Prevation in Darussalam Health Preventation Lhokseumawe City - Wulandari Wulandari; Samsidar Sitorus; Aida Fitria (Newinera Publisher, 2020)
According to Republic of Indonesia Minister of Health Regulation Number 52 of 2017, health development is aimed at increasing awareness, willingness and ability to live healthy for everyone so that the highest degree of public health can be realized as an investment for the development of productive human resources. This research is Quasy experiment with one-group-pretest and posttest without a control group which describes the effect of health education through the HIV/AIDS booklet media on adolescent behaviour. The population were 71 people, and all were as the sample. Based on the Wilcoxon Signed Rank test, the significance value is 0.000 <.05. Based on the multivariate analysis with the MANOVA test, it was found that the attitude variable (R-Square = .773) was the variable that had the strongest correlation with the experiment giving the HIV/AIDS booklet media. The results showed the effect of health education through the HIV/AIDS Booklet Media on changes in adolescent behaviour for HIV/AIDS prevention, indicated by an increase in knowledge, attitudes and actions before and after the distribution of HIV/AIDS booklets. Increasing the implementation of HIV/AIDS socialization activities for vocational high school youth by providing education using media tailored to educational targets, one of which is the HIV/AIDS booklet media for vocational high school students and students as a preventive effort in reducing HIV/AIDS cases among vocational high school adolescents so that teenagers in this school become liaison information related to HIV/AIDS to adolescents in other schools.